The effect of corporate tax avoidance on the cost of equity - GOH, Beng Wee (Institutional Knowledge at Singapore Management University, 2013)
While prior studies have examined how investors perceive extreme forms of tax avoidance behavior such as tax sheltering and uncertain tax position (e.g., Hanlon and Slemrod 2009; Wilson 2009; Koester 2011; Hutchens and Rego 2012), there is little evidence on how investors perceive less extreme forms of tax avoidance. This study fills this void by examining the relation between firm’s cost of equity and corporate tax avoidance using three measures that capture less extreme forms of corporate tax avoidance: book-tax differences, permanent book-tax differences, and long-run cash effective tax rates. We find that less aggressive forms of corporate tax avoidance significantly reduces a firm’s cost of equity. Further analyses reveal that this effect is stronger for (i) firms with better outside monitoring, (ii) firms that likely realize higher marginal benefits from tax savings, and (iii) firms with better information quality. Our study presents large-sample results on how investors perceive less aggressive corporate tax avoidance and shows that tax planning is a value-enhancing activity for shareholders.